2022
DOI: 10.3390/ijerph191710815
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Body Posture Abnormalities in Relation to the Segmental Body Composition in Early School-Aged Children

Abstract: Children are exposed to multiple factors that contribute to an increase in body mass and the development of posture defects. The aim of the study is to assess the relationship between the segmental distribution of fat mass and muscle mass and the incidence of body posture abnormalities in early school-aged children. A total of 190 children aged 7–9 were included in the research project. The examined children were divided according to age (class level) into three groups. Height, weight and body composition, BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The larger the recorded gamma heel angle, the more developed the muscles of the examined limb were, and consequently, the foot structure was more likely to be normal. Ziętek et al showed the importance of using segmental body composition analysis as a screening method for posture defects, and that muscle mass and percentage of body fat play a crucial role in development of correct body posture in young school-age children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The larger the recorded gamma heel angle, the more developed the muscles of the examined limb were, and consequently, the foot structure was more likely to be normal. Ziętek et al showed the importance of using segmental body composition analysis as a screening method for posture defects, and that muscle mass and percentage of body fat play a crucial role in development of correct body posture in young school-age children [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ziętek et al demonstrated that the balance between muscle mass and the percentage of body fat plays a crucial role in shaping correct body posture, including proper foot structure [ 28 ]. Increased fat mass around the foot in preschool-age children indicates the presence of a fat pad typical for this age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations